Lipoproteins Contribute to the Anti-inflammatory Capacity of Lactobacillus plantarum WCFS1 - Lee, I-Chiao; van Swam, Iris I.; Boeren, Sjef; Vervoort, Jacques; Meijerink, Marjolein; Taverne, Nico; Starrenburg, Marjo; Bron, Peter A.; Kleerebezem, Michiel (Frontiers in Microbiology, 2020)
Bacterial lipoproteins are well-recognized microorganism-associated molecular patterns, which interact with Toll-like receptor (TLR) 2, an important pattern recognition receptor of the host innate immune system. Lipoproteins are conjugated with two- or three-acyl chains (di- or tri-acyl), which is essential for appropriate anchoring in the cell membrane as well as for the interaction with TLR2. Lipoproteins have mostly been studied in pathogens and have established roles in various biological processes, such as nutrient import, cell wall cross-linking and remodeling, and host-cell interaction. By contrast, information on the role of lipoproteins in the physiology and host interaction of probiotic bacteria is scarce. By deletion of lgt, encoding prolipoprotein diacylglyceryltransferase, responsible for lipidation of lipoprotein precursors, we investigated the roles of the collective group of lipoproteins in the physiology of the probiotic model strain Lactobacillus plantarum WCFS1 using proteomic analysis of secreted proteins. To investigate the consequences of the lgt mutation in host-cell interaction, the capacity of mutant and wild-type bacteria to stimulate TLR2 signaling and inflammatory responses was compared using (reporter-) cell-based models. These experiments exemplified the critical contribution of the acyl chains of lipoproteins in immunomodulation. To the best of our knowledge, this is the first study that investigated collective lipoprotein functions in a model strain for probiotic lactobacilli, and we show that the lipoproteins in L. plantarum WCFS1 are critical drivers of anti-inflammatory host responses towards this strain.